The Effectiveness of Implementation of Online Single Submission (OSS) at the Investment and One-Stop Integrated Service Agency of Pontianak City - Erice Yuldwiva Eris; Dwi Nur Handayani; Lina Sunyata; Annisa Rizqa Alamri; Taufik Akbar (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2026)
This thesis examines the effectiveness of the Online Single Submission (OSS) system in Pontianak City. The research seeks to analyze how effective OSS supports business licensing services at the Investment and One-Stop Integrated Service Agency (IOSISA) of Pontianak City. OSS represents a government-led digital innovation designed to streamline licensing procedures, particularly following the enactment of Government Regulation No. 5 of 2021 on Risk-Based Licensing. This study employed a descriptive qualitative approach, drawing on Duncan’s theory of effectiveness, which encompasses three dimensions: Goal Achievement, Integration, and Adaptation. The findings indicate that, in terms of goal achievement, OSS has expedited the issuance of low-risk business licenses and enhanced the legal standing of business actors, although challenges remain in users’ comprehension of the system and in the length of time required for verifying medium-to high-risk licenses. With respect to integration, the system offers more structured procedures; however, socialization efforts have not been evenly distributed, and updates from the central system are often poorly communicated. In terms of adaptation, IOSISA has demonstrated a relatively responsive approach, supported by adequate infrastructure, despite occasional technical disruptions. The novelty of this research lies in its focus on assessing the effectiveness of OSS in the local context of Pontianak City, an area that has received little scholarly attention. As such, the study provides valuable insights and practical recommendations for improving business licensing services at the regional level.